ERAP1 overexpression in HPV-induced malignancies: A possible novel immune evasion mechanism. (3rd July 2017) - Steinbach, Alina; Winter, Jan; Reuschenbach, Miriam; Blatnik, Renata; Klevenz, Alexandra; Bertrand, Miriam; Hoppe, Stephanie; von Knebel Doeberitz, Magnus; Grabowska, Agnieszka K.; Riemer, Angelika B.
ABSTRACT: Immune evasion of tumors poses a major challenge for immunotherapy. For human papillomavirus (HPV)-induced malignancies, multiple immune evasion mechanisms have been described, including altered expression of antigen processing machinery (APM) components. These changes can directly influence epitope presentation and thus T-cell responses against tumor cells. To date, the APM had not been studied systematically in a large array of HPV + tumor samples. Therefore in this study, systematic expression analysis of the APM was performed on the mRNA and protein level in a comprehensive collection of HPV16 + cell lines. Subsequently, HPV + cervical tissue samples were examined by immunohistochemistry. ERAP1 (endoplasmic reticulum aminopeptidase 1) was the only APM component consistently altered – namely overexpressed – in HPV16 + tumor cell lines. ERAP1 was also found to be overexpressed in cervical intraepithelial neoplasia and cervical cancer samples; expression levels were increasing with disease stage. On the functional level, the influence of ERAP1 expression levels on HPV16 E7-derived epitope presentation was investigated by mass spectrometry and in cytotoxicity assays with HPV16-specific T-cell lines. ERAP1 overexpression did not cause a complete destruction of any of the HPV epitopes analyzed, however, an influence of ERAP1 overexpression on the presentation levels of certain HPV epitopes could be demonstrated by HPV16-specific CD8 + T-cells. These showed enhanced killing toward HPV16 + CaSki cells whose ERAP1 expression had been attenuated to normal levels. ERAP1 overexpression may thus represent a novel immune evasion mechanism in HPV-induced malignancies, in cases when presentation of clinically relevant epitopes is reduced by overactivity of this peptidase.